Pengaruh Fomo, Loss Aversion dan Herding Behavior Terhadap Keputusan Berinvestasi Emas di Bank Syariah Indonesia - Sella Wijayanti; Supriyanto Supriyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of Fomo, Loss Aversion and Herding Behavior on gold investment decisions at Bank Syariah Indonesia, both partially and simultaneously. This study focused on the millennial generation in Klaten Regency. This study used a quantitative method with 150 respondents who had invested in gold at Bank Syariah Indonesia. The data analysis technique used multiple linear regression. The results revealed that Fomo partially had no significant effect on investment decisions. Loss Aversion had a negative and significant effect on investment decisions, while herding behavior had a positive and significant effect on investment decisions. Simultaneously, these three variables significantly influenced gold investment decisions at Bank Syariah Indonesia. With a coefficient of determination (R2) of 0.123, indicating that 12.3% of the variation in investment decisions was explained by the research variables, but the remainder was influenced by other factors. This study explains the importance of psychological and social factors in behavioral finance theory in the investment decisions of the millennial generation in gold investment decisions.